Peningkatan Minat Pertanian melalui Farming Education untuk Petani Cilik (PECI) Desa Bicak - Airlangga, Primaadi; Susanti, Ambar; Nasirudin, Mohamad; Krisdianto, Achmad; Kiswanto, Budi; Bella, Leila; Fitri, Ursila (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
UNWAHA's community service program, in an effort to Increase Interest in Agriculture through Farming Education for Young Farmers (Petani Cilik = PECI), was implemented at SDN Bicak, Trowulan District, Mojokerto. It was implemented on August 15 - September 1, 2025, with 25 fourth-grade students of SDN Bicak. The activity aimed to foster interest and awareness of the young generation from an early age towards the agricultural sector, so that it could become a career choice as well as a useful activity. The outputs are: 1) The formation of the PECI, which is an important step in fostering children's interest and concern for the world of agriculture, 2) children have the opportunity to learn how to manage plants starting from the process of planting, caring for, harvesting, and making simple Liquid Organic Fertilizer (LOF). The method applied is a combination of direct practical education and participation of the surrounding village community, literature study methods, and Participatory Learning and Action (PLA). The results obtained are that the PECI Program can encourage students to be able to recognize and practice simple farming methods. The UNWAHA community service Program in Bicak Village was successful in increasing agricultural interest and skills through the Little Farmer training, as evidenced by the increase in the average post-test score compared to the pre-test. This program serves as a means of education and early development so that they grow into the next generation of farmers who care about the environment.